The Role of Personal Branding on Social Media in Shaping Gen Y & Z’s Life Insurance Purchase Decisions in Indonesia - Lukmandjaja, William (Digital Repository of Theses, 2025)
This study explores the role of personal branding on social media in influencing Gen Y and Z consumers’ perceptions and purchase intentions of life insurance products in Indonesia. Despite personal branding’s success in industries such as entertainment and entrepreneurship, its potential within the life insurance sector remains underutilized, especially in the Indonesian market. With low national insurance penetration and increasing interest in financial security among younger generations, this research examines how Indonesian insurance agents can leverage personal branding on social media to build trust, stand out, and ultimately drive consumer engagement. Employing a quantitative approach, this study gathered data from surveys distributed to 243 Indonesian Gen Y and Z consumers, a demographic representing a growing market for insurance products. Analysis through Structural Equation Modeling-Partial Least Squares (SEM-PLS) validated the hypotheses, demonstrating positive relationships between agents’ personal branding efforts on social media and increased consumer trust, positive perception, and purchase intent towards insurance. This study applies the personal branding theory (Rachmad, 2023). The theory suggests that personal branding is for everyone who wishes professional success. Moreover, it is important that authenticity, authority, visibility and consistency on social media to be taken seriously combined with professional networking strategy and collaboration between personal brands in order to build trust on social media. Finding reveals that young Indonesian consumers are significantly influenced by insurance agents who present a consistent, professional, and relatable social media presence. These agents are perceived as more trustworthy and knowledgeable, which leads to a higher likelihood of consumer engagement and product purchases in the future. This research contributes to both academic understanding and industry practice by highlighting the impact of social media branding as a strategic tool for insurance agents to build relationships and differentiate themselves in a competitive field. Ultimately, it provides actionable insights for insurance agents aiming to start their social media presence to increase consumer loyalty and drive sales within Indonesia’s emerging insurance market. keywords : insurance, social media, personal branding, consumer behavior, digital marketing, branding, next generation, content marketing.